Al-Takamul al-ma'rifi wa-afaq tajdid al-fikr al-Islami = Integration of knowledge and the horizons of Islamic thought renewal - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2013)
This is the second book about integration of knowledge in the modern world. It consists of proceedings of International Conference on Islamization in Modern Science and Scientification of the Studies in Islamic Revealed Knowledge (ICIMSIS), Organized by Kulliyyah of Science, IIUM, on December 2011. The book discues issues of integration and Islamization of knowledge from various dimensions.